2008
DOI: 10.3174/ajnr.a0997
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Stenosis of the Carotid Artery Associated with Ipsilateral Cerebrovascular Events

Abstract: BACKGROUND AND PURPOSE:Eccentric stenosis of the coronary artery is associated with plaque disruption and acute coronary syndrome. The purpose of the present study was to determine whether eccentric stenosis of the carotid artery contributes to cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…8 As for clinical relevance of plaque eccentricity, a clinical study on carotid plaques suggested that eccentric plaque is a potential marker for ipsilateral cerebrovascular events. 4 Our present study on histology-verified ICAD, however, failed to indicate the association between eccentric intracranial atherosclerotic plaques and brain infarctions, in spite of seemingly higher incidence of brain infarction due to eccentric plaques rather than concentric plaques. Further studies are needed to clarify the morphological features of ICAD and to explore their clinical relevance.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…8 As for clinical relevance of plaque eccentricity, a clinical study on carotid plaques suggested that eccentric plaque is a potential marker for ipsilateral cerebrovascular events. 4 Our present study on histology-verified ICAD, however, failed to indicate the association between eccentric intracranial atherosclerotic plaques and brain infarctions, in spite of seemingly higher incidence of brain infarction due to eccentric plaques rather than concentric plaques. Further studies are needed to clarify the morphological features of ICAD and to explore their clinical relevance.…”
Section: Discussioncontrasting
confidence: 39%
“…3 Recent clinical trial studies on carotid arteries showed that, in addition to luminal stenosis, plaque eccentricity (symmetry) is among the plaque features associated with more frequent cerebrovascular events. 4 The aim of the current study was to investigate the eccentricity of histology-verified intracranial atherosclerotic lesions on 1.5T MRI vessel wall imaging and its potential clinical implications. …”
mentioning
confidence: 99%
“…Previous studies showed that for carotid plaques, larger maximum wall thickness and eccentric plaques were associated with the occurrence of subsequent cerebrovascular events1617. For intracranial vascular disease, eccentric wall thickening has been used to distinguish intracranial atherosclerosis from other etiologies1819.…”
Section: Discussionmentioning
confidence: 99%
“…TVA, LA, and WA reflect the severity of carotid atherosclerosis in outward remodeling, lumen reduction, and plaque burden [20]. Luminal Max-stenosis remains the main indictor for assessing the clinical risk from carotid atherosclerotic disease [21]. Recent studies have shown that NWI measurement may more accurately present the severity of carotid atherosclerosis [22].…”
Section: Discussionmentioning
confidence: 99%